Controversies about human origins - Preliminary analysis of a students' questionnaire - Tomczyk, Jacek; Bugajak, Grzegorz (Studia Ecologiae et Bioethicae, 2007)
The paper presents the results of the research which was carried out as a part of the project: Current controversies about human origins. Between anthropology and the Bible, this project was focused on the supposed conflict between natural sciences and theology (or religious beliefs) with regard to the origin of man. The research was aimed at finding out whether such a conflict really exits. For we cannot exclude the possibility that these controversies have no factual ground and their significance is inflated by American popular literature. If, on the other hand, we assume that the conflict is real, it should be worthwhile examining its sources. Such an approach may prove helpful in systematize the highly emotional debates about the origin of man. One of the ways of tackling the issue was a questionnaire which was distributed among students, teachers and university professors. Our respondents represented three disciplines: theology, philosophy and natural sciences, t t e paper presents selected results of the questionnaire which was addressed to a group of students, they were asked to fill in the form consisting of eleven questions, these questions concerned the following issues: the existence of the conflict between evolutionism and creationism, the definitions of creation and evolution, the existence of the spiritual element in man, and the ways of interpreting the Bible (esp. the first chapters of the Book of Genesis).